Determining the Contribution of Exercise in Preventing Aberrant Myelopoiesis with Obesity and its Implications for Colorectal Cancer Onset - Vanhie, James Joseph George (Université d'Ottawa | University of Ottawa, 2024)
Obesity continues in its severity on a global scale, where by 2030 it is anticipated that a third of adults will be overweight and another half will be classified as having obesity1. Several components contribute to the elevating trend; a lack of physical activity and Western diet consumption are at the forefront2. Western diets are rich in saturated fats that promote adipocyte hypertrophy and chronic low-grade systemic inflammation that is driven by aberrant myelopoiesis in the bone marrow2–6. The bone marrow is a complex environment that hosts hematopoiesis—the process of blood cell formation. Hematopoietic stem cells (HSCs) are the most primitive pluripotent cells that can divide asymmetrically to form more committed progenitor cells of the lymphoid and myeloid lineages. Our lab has previously demonstrated that high-fat diet-induced obesity promotes inflammatory myeloid cell formation, termed myelopoiesis, that is attenuated by exercise training under conditions of radiation-induced stress hematopoiesis7. Previous reports suggest that cells in the HSC niche could be communicating via extracellular vesicles to affect myelopoiesis8,9. Therefore, obesity may alter EV signaling, and by extension, myelopoiesis. Targeting obesity-induced aberrant myelopoiesis through exercise training could have important implications for peripheral disease. Colorectal cancer (CRC) is being diagnosed at ever increasing rates in young people that is due, in part, to Western diet consumption alongside a sedentary lifestyle10–12. Since obesity also promotes chronic low-grade inflammation and aberrant myelopoiesis, obesity may promote CRC onset through these mechanisms. A previous report demonstrated a partial reliance on macrophage accumulation in CRC development, where transient macrophage depletion attenuated carcinogenesis13. Importantly, our group14 and others15 have shown that weight loss alone does not attenuate CRC formation. Instead, we reported previously that colorectal carcinogenesis is mitigated only with the introduction of exercise alongside weight loss14. However, whether inflammatory cell accumulation is marrow-derived and precedes colorectal carcinogenesis and localized inflammation remains unknown. Further, alterations to EV communication and HSC differentiation patterns during steady state hematopoiesis remain unknown. Therefore, the overall objective of the thesis was to deepen our understanding of how obesity and exercise exert differential effects on steady state hematopoiesis, and in turn, whether the differential effects of obesity and exercise on hematopoiesis underlie colon cancer aetiology. Our main findings were that obesity promotes HSC and progenitor cell expansion alongside aberrant myelopoiesis during steady state hematopoiesis. EVs had altered cargo, where miRNA-331-5p and miR-193 were lower in EVs derived from exercised mice with obesity compared to sedentary counterparts. Further, EVs from exercised mice with obesity attenuated HSC and progenitor cell expansion that was observed in sedentary counterparts. Finally, obesity led to enhanced myeloid cell accumulation in the colon without any effect of exercise, yet exercise attenuated colorectal carcinogenesis, which may be due to β-Catenin and STAT3 molecular pathway maintenance. Overall, the current thesis found that high-fat diet-induced obesity alters HSC niche EV communication, promotes aberrant myelopoiesis and colon myeloid cell accumulation, and colon cancer formation. However, exercise training attenuates aberrant myelopoiesis and colon cancer formation, which may be due to cell proliferation pathway management.
Keywords: Hematopoiesis; Extracellular Vesicle; High-Fat Diet; Mouse